2017
DOI: 10.1038/ctg.2016.63
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Gut–brain Axis in Regulating Glucose Metabolism After Acute Pancreatitis

Abstract: Objectives:Diabetes has become an epidemic in developed and developing countries alike, with an increased demand for new efficacious treatments. A large body of pre-clinical evidence suggests that the gut–brain axis may be exploited as a potential therapeutic target for defective glucose homeostasis. This clinical study aimed to investigate a comprehensive panel of glucoregulatory peptides, released by both the gut and brain, in individuals after acute pancreatitis.Methods:Fasting levels of glucagon-like pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 56 publications
1
29
1
Order By: Relevance
“…The absolutely novel finding is that, for every ng/mL change in oxyntomodulin, intra‐pancreatic fat significantly decreased by 0.21%. Oxyntomodulin is a 37‐amino acid peptide (secreted by enteroendocrine L cells and the central nervous system) that acts as an agonist for GLP‐1 and glucagon receptors . Previous clinical studies have demonstrated that exogenous administration of oxyntomodulin regulates energy intake, decreases body weight, and affects adipose tissue hormones .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absolutely novel finding is that, for every ng/mL change in oxyntomodulin, intra‐pancreatic fat significantly decreased by 0.21%. Oxyntomodulin is a 37‐amino acid peptide (secreted by enteroendocrine L cells and the central nervous system) that acts as an agonist for GLP‐1 and glucagon receptors . Previous clinical studies have demonstrated that exogenous administration of oxyntomodulin regulates energy intake, decreases body weight, and affects adipose tissue hormones .…”
Section: Discussionmentioning
confidence: 99%
“…Oxyntomodulin is a 37-amino acid peptide (secreted by enteroendocrine L cells and the central nervous system) that acts as an agonist for GLP-1 and glucagon receptors. 16 Previous clinical studies have demonstrated that exogenous administration of oxyntomodulin regulates energy intake, decreases body weight, and affects adipose tissue hormones. 17 To date, no study has investigated the association between IFD and circulating levels of oxyntomodulin.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have reported the relationship between the brain and the GI system, the so-called gut-brain axis or brain-gut axis. It has been hypothesized that GI dysfunctions could reflect the disruptions of the microbiome-gut-brain axis, leading to serious GI inflammatory diseases (e.g., acute pancreatitis or inflammatory bowel disease), endothelial dysfunction, altered immune functioning and regulation of appetite control, neural inflammation, subsequent neurodegeneration, cognitive or psychoneurological disorders (e.g., depression, anxiety, autism, dementia), and disease progression of PD [8][9][10][11][12][13][14][15][16][17][18][19]. In addition to the use of peptides for the improvement of gastrointestinal or digestive dysfunctions [13,[20][21][22], and in order to improve GI function and the balance of microbiota, probiotics could be one of the powerful tools to be used for altering the PD-associated microbiota composition and mitigating the related inflammatory process [12,23].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from pre-clinical studies suggests that CGRP stimulates insulin secretion (29)(30)(31) in a dose-dependent manner while data from clinical studies show an inhibitory effect of CGRP on insulin secretion (32,33). Recent studies suggest that certain pancreatic [insulin, amylin, pancreatic polypeptide (PP)] and gut hormones (glicentin, oxyntomodulin) are altered in patients with abnormal glucose metabolism after acute pancreatitis (20,21,34). There is sufficient evidence, spanning nearly two decades, on the influence of CGRP on the secretion of pancreatic and gut hormones, in particular glucagon, somatostatin, and glucagon like peptide (GLP)-1 (26,27,35,36).…”
Section: Introductionmentioning
confidence: 99%